2018
DOI: 10.1007/s10068-018-0364-7
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, total phenolic and flavonoid contents, and antioxidant potential of seeds and sprouts of Korean peanuts

Abstract: Peanut sprouts are gaining increasing popularity as a potential source of functional food. The objective of this study was to investigate yield and food value of peanut sprouts of six Korean peanut genotypes (Daekwang, Akwang, Baekjung, Alogi, Pungan and Heugttangkong) from day 5 through 9. Functional compounds like polyphenol, flavonoid, and resveratrol contents were significantly (p\0.05) high in the sprouts compared to those in the seeds. Pungan yielded significantly (p\0.05) high sprouts followed by Alogi.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 30 publications
3
39
0
4
Order By: Relevance
“…The method described by Adhikari et al [ 44 ] was used to measure polyphenol content. In brief, samples were extracted with 100% methanol and measured using a spectrophotometer (Multiskan GO; Thermo Fisher Scientific, Waltham, MA, USA) at 750 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The method described by Adhikari et al [ 44 ] was used to measure polyphenol content. In brief, samples were extracted with 100% methanol and measured using a spectrophotometer (Multiskan GO; Thermo Fisher Scientific, Waltham, MA, USA) at 750 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The total phenolic content (TPC) was determined by the Folin-Ciocalteu method, as previously described [15], and the results were expressed as milligrams of gallic acid equivalent (mg GAE)/100 g DW of samples. Total flavonoid content (TFC) was determined by the AlCl 3 -based colorimetric method, as previously described [8], and the results were expressed as mg catechin equivalent (CE mg)/100 g dry weight (DW) of samples.…”
Section: Methodsmentioning
confidence: 99%
“…Peanut seeds and germinated peanuts are nutritious and have high medicinal and economic values [7]. It has been reported that germinated peanut contains higher levels of flavonoids and other phenolic compounds than peanut seeds [8]. Especially, compared to peanut seeds, germinated peanuts exhibit enhanced antioxidant activity [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, sprouts and microgreens have recently gained popularity as easy-to-produce (e.g., small size, without soil and external inputs as fertilizers and pesticides), healthy gastronomic ingredients [ 12 , 13 ]. Indeed, compared to mature-leaf crops, they contain a higher amount of bioactive compounds, antioxidants, minerals, and phytonutrients [ 14 ]. Their consumption has been associated with a reduced risk of cancer, respiratory problems, osteoporosis, and muscle atrophy, which are frequent diseases associated with obesity and malnutrition [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%